Pemberdayaan Masyarakat Desa Montong Ajan melalui Pengelolaan Wisata Air Terjun Rumpang Rumeneng dan Pengembangan Produk Ekonomi Kreatif Berbasis Potensi Lokal - samsul hadi (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Politeknik Negeri Banyuwangi, 2026)
This community service activity was carried out in Montong Ajan Village, Praya Barat Daya Subdistrict, Central Lombok Regency, with the aim of increasing the capacity of the community in managing the Rumpang Rumeneng Waterfall natural tourism site and developing creative economy products based on local potential. The method used was the Participatory Action Approach through the stages of training, mentoring, and participatory evaluation. The training focused on improving destination management skills, hospitality principles, and the development of local products such as bamboo crafts and culinary products unique to the village. Mentoring was carried out through regular field visits to help the community apply the skills they had acquired, strengthen the Pokdarwis institution, and foster collective awareness of the importance of sustainable tourism management. The results of the activities show an increase in the community's capacity in tourism management, the formation of new creative business groups, and increased social and economic participation of the village community. This program has succeeded in strengthening the synergy between the tourism and creative economy sectors as an effort to empower the community based on local potential. This activity is expected to become a model for the development of competitive and sustainable tourism villages in the Central Lombok region.